Bifluoride Ion Mediated SuFEx Trifluoromethylation of Sulfonyl Fluorides and Iminosulfur Oxydifluorides. (27th February 2019) - Smedley, Christopher J.; Zheng, Qinheng; Gao, Bing; Li, Suhua; Molino, Andrew; Duivenvoorden, Hendrika M.; Parker, Belinda S.; Wilson, David J. D.; Sharpless, K. Barry; Moses, John E.
Abstract: SuFEx is a new‐generation click chemistry transformation that exploits the unique properties of S−F bonds and their ability to undergo near‐perfect reactions with nucleophiles. We report here the first SuFEx‐based procedure for the efficient synthesis of pharmaceutically important triflones and bis(trifluoromethyl)sulfur oxyimines from sulfonyl fluorides and iminosulfur oxydifluorides, respectively. The new process involves rapid S−F exchange with trifluoromethyltrimethylsilane (TMSCF3 ) upon activation by potassium bifluoride in anhydrous DMSO. The reaction tolerates a wide selection of substrates and proceeds under mild conditions without need for chromatographic purification. A tentative mechanism is proposed involving nucleophilic displacement of S−F by the trifluoromethyl anion via a five‐coordinate intermediate. The utility of late‐stage SuFEx trifluoromethylation is demonstrated through the synthesis and selective anticancer properties of a bis(trifluoromethyl)sulfur oxyimine. Abstract : Eine SuFEx‐Trifluormethylierung von Sulfonylfluoriden und Iminoschwefeloxyfluoriden wird beschrieben. Effizienter S‐F‐Austausch mit TMSCF3 wird durch substöchiometrische Mengen von Bifluorid [FHF] − in wasserfreiem DMSO ausgelöst. Die bislang unzugänglichen Bis(trifluormethyl)schwefeloxyimine zeigen Antitumorwirkung.